2003
DOI: 10.1007/s10126-002-0065-2
|View full text |Cite
|
Sign up to set email alerts
|

UV-Absorbing Substance in the Red Alga Porphyra yezoensis (Bangiales, Rhodophyta) Block Thymine Photodimer Production

Abstract: The effect of the water-soluble UV-absorbing substance (UVAS) extracted from the marine red alga Porphyra yezoensis Ueda on UV-dependent thymine photodimer production was investigated. The T<>T pyrimidine-pyrimidone 6-4 dimer and the cyclobutane cis-syn T<>T 5-6 dimer produced by UV irradiation with a xenon lamp were analyzed by reverse-phase high-performance liquid chromatography. Although the dimer production was reduced when the irradiation was filtered through a UVAS solution, it decreased more when thymin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 7 publications
0
69
0
5
Order By: Relevance
“…When the corresponding s is irradiated (Fig. 4, d), strong NOEs appear at two of the four d of CH 2 (8) and CH 2 (10). Hence, these protons must be the ones cis to the CH 2 OH group and are thus attributed to H R ÀC(8) and H S ÀC(10).…”
Section: ) Hmentioning
confidence: 93%
See 1 more Smart Citation
“…When the corresponding s is irradiated (Fig. 4, d), strong NOEs appear at two of the four d of CH 2 (8) and CH 2 (10). Hence, these protons must be the ones cis to the CH 2 OH group and are thus attributed to H R ÀC(8) and H S ÀC(10).…”
Section: ) Hmentioning
confidence: 93%
“…UV-Absorbing compounds from Porphyra yezoensis were found to block very efficiently the formation of thymine dimers, an important form of UV-induced DNA damage. For this protective effect, some kind of energy transfer from excited states of thymine to MAA molecules was proposed; however, the exact mechanism is unclear [10]. There are also effects of 1 other than UV absorption that are related to oxygen metabolism.…”
mentioning
confidence: 98%
“…These compounds may be of great value in the development of artificial sunscreens and a source for future biotechnological research. Misonou et al (2003) has observed that MAAs can block the production of both 6-4 photoproduct and cyclobutane pyrimidine dimer (CPD) formation. MAA extracted from red alga Porphyra umbilicalis demonstrated in in-vitro studies a DNAprotecting effect and the viability enhancing properties (Schmid et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Misonou et al (2003) studied the protective effects of MAAs against DNA damage and found that they were able to effectively block thymine dimer formation by UV radiation. Oyamada et al (2008) examined the protective effects of three different kinds of MAAs (shinorine, porphyra-334 and mycosporine-glycine) on human fibroblast cells and found that all three protected the cells from UV-induced cell death, with mycosporine-glycine having the strongest effect.…”
Section: Mycosporine-like Amino Acids (Maas)mentioning
confidence: 99%